Risking everything : a Freedom Summer reader - Edmonds, Michael, 1952- (Wisconsin Historical Society Press, 2014)
"Risking Everything : A Freedom Summer Reader documents the 1964 Mississippi Freedom Summer Project, when SNCC and CORE workers and volunteers arrived in the Deep South to register voters and teach non-violence, and more than 60,000 Black Mississippians risked everything to overturn a system that had brutally exploited them. In the 44 original documents in this anthology, you'll read their letters, eavesdrop on their meetings, shudder at their suffering, and admire their courage. You'll witness the final hours of three workers murdered on the project's first day, hear testimony by Black residents who bravely stood up to police torture and Klan firebombs, and watch the liberal establishment betray them. These vivid primary sources, collected by the Wisconsin Historical Society, provide both first-hand accounts of this astounding grassroots struggle as well as a broader understanding of the Civil Rights movement. The selected documents are among the 25,000 pages about the Mississippi Freedom Summer Project in the archives of the Wisconsin Historical Society. The manuscripts were collected in the mid-1960s, at a time when few other institutions were interested in saving the stories of common people in McComb or Ruleville, Mississippi. Most have never been published before"--